A model for research supervision of international students in engineering and information technology disciplines : final report. - Yarlagadda, Prasad (Office for Learning and Teaching, 2013)
There is increasing enrolment of international students in the engineering and information technology disciplines and anecdotal evidence of a need for additional understanding and support for these students and their supervisors due to differences both in academic and social cultures. This project aimed to identify a set of factors influencing the success of culturally and linguistically diverse (CALD) Higher Degree Research (HDR) students in engineering & information technology (IT) disciplines in order to provide effective supervision and support services. [Executive summary]